The Role Of Marketing Audit In Yotta Beverage Business In Makassar, Pettarani Branch - Sangkala, Masnawaty (PT. Maju Malaqbi Makkarana, 2023)
This study aims to find out information related to the implementation of Marketing Audit in the Yotta beverage business in Makassar. In a marketing audit examination it can be said as a mechanism with the aim of being able to carry out the process of collecting information and being able to analyze data related to the external and internal environment, which is inseparable from several indicators including economic conditions, the level of market competition and the level of business operations. The application of marketing audits is a type of functional marketing audit in the Yotta beverage business with components including marketing environment audits, marketing strategy audits, marketing organization audits, marketing system audits, marketing productivity audits, marketing function audits. The method used in this research uses quantitative research methods with the data used obtained using questionnaires and library data. The results of this study indicate that the marketing audit components of Yotta's beverage business consist of marketing environment audits, marketing strategy audits, marketing organization audits, marketing system audits, marketing productivity audits, marketing function audits play a very important role.